Spirit and the politics of disablement - Betcher, Sharon V. (Fortress Press, 2007)
Preface -- Introduction: telling it slant -- The fear of falling -- Monstrosity, miracle, and mission : religion and the politics of disablement -- Medicine shows : humanitarianism, healing, and the physics of spirit -- Putting my foot (prosthesis, crutches, phantom) down : technology as transcendence -- Conspicuous compassion : race, "disability," and salvific imperialism -- A Crip nation -- Rumor mills : spiritual practice in the Crip nation -- "A cripple on this bridge" : thinking difference, thinking differently -- Never quite herself again : Frida Kahlo's doctrine of creation -- Wisdom to make the world go on